O Traço de Mindfulness como Protector nos Comportamentos Bulímicos - Duarte, Cristiana (2010)
This study aims to understand the predictive power of mindfulness trait in the context of bulimic behaviors. A battery of self-report questionnaires was used to assess mindfulness trait, bulimia, body dissatisfaction, social comparison and of physical appearance and shame, in a non-clinical sample of 354 university students and 297 women from general population, and a clinical sample of 42 patients with eating disorders. Results show that, in both groups, there’s an association between lower levels of mindfulness trait and psychopathology. In the clinical sample, it is seen that a binge eating pattern is associated with lower levels of mindfulness trait. The mindfulness facets of Acting with Awareness and Nonjudging of Experience significantly predict bulimic behaviors. These findings suggest that mindfulness trait can have a protective role on the development of an eating disorder, revealing new therapeutic possibilities in the treatment of such disorders.